Agriculture In the Southeast Region of Romania: An Outlook of Farms and Employees - Beatrice-Simona MANOLACHE; Constantin MANOLACHE; Silvius STANCIU (Communications of International Proceedings, 2022)
The analysis of Romania's agricultural sector is a current topic, being studied over time from different points of view and through the prism of different impact factors. The paper proposes an assessment of the agricultural potential of the South East Development Region of Romania, from the perspective of regional development strategies. It was found that the analyzed area is a predominantly agricultural region, with characteristics and high development potential, but which falls within the existing general situation at the national level. It was found that the analyzed area is a region with a predominantly agricultural economy, having natural characteristics and high development potential, but which falls within the existing general situation at national level. In the region there are artisanal food processing units, which favored the development of traditional products, such as Pleșcoi sausages. The presence of the Carpathian Mountains in the region may have potential for the development of mountain products. The fragmentation of agricultural land, the lack of a viable irrigation system, the need for investments in infrastructure are the main aspects resulting from the research.
Keywords: agriculture; South East Development Region of Romania; development strategies